TANGGUNG JAWAB KELUARGA, SEKOLAH, DAN MASYARAKAT DALAM PENDIDIKAN: Responsibility of Family, School, and Society in Education - Zainuddin (IAI DDI Mangkoso, 2022)
This study aims to develop the results of previous studies with a view to knowing the responsibilities of families, schools, and communities in education. This research is library research using educational and psychological approaches. Sources of data are taken from primary data in the form of books or books that have relevance to the title discussed, from these references are analyzed and then concluded. The results of the study reveal that family responsibility in education is very meaningful, because the family is the first and foremost educational institution for children to get guidance to grow up with personality, intelligence, and skills. Then, the responsibility of the school is the continuation of the family education process. Therefore, school education institutions must be able to maximize their role so that the academic potential of students can develop, and the responsibility of the community is as a place for socialization, social control, cultural preservation, educational selection and social change, and as an educational institution. The implications of research on family, school, and community responsibilities in education have their respective roles to make children spiritually, intellectually intelligent, and also develop their psychomotor aspects. Family education institutions as the beginning of children getting education from both parents by introducing that God is the creator of everything in this world, educating their children so that they have noble character, then, school as a continuation of education that takes place in the family to shape children's academic intelligence. Then, the community contributes as a place for socialization and cultural.